A Prediction Model for Chemotherapy-Induced Thrombocytopenia Based on Real-World Data and a Close Relationship Between AST/ALT Ratio and Platelet Count in Patients with Solid Tumors [Corrigendum] - Song B; Zhou S; Li C; Zheng H; Zhang X; Jin X; Fu J; Hu H (International Journal of General Medicine, 2022)
Song B, Zhou S, Li C, et al. Int J Gen Med. 2022;15:8003–8015. The authors have advised the author and affiliations list on page 8003 is incorrect. The correct details are as follows. Bingxin Song,1,2 Shishi Zhou,1 Chenghui Li,1 Hongjuan Zheng,1 Xia Zhang,1 Xiayun Jin,1 Huixian Hu,2 Jianfei Fu1 1Department of Medical Oncology, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, Zhejiang Province, People’s Republic of China; 2Department of Medical Hematology, Affiliated Jinhua Hospital, Zhejiang University School of Medicine, Jinhua, Zhejiang Province, People’s Republic of China. The authors apologize for the errors.